2013
DOI: 10.1111/ajo.12053
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of successful expectant management of first trimester miscarriage: Development and validation of a new mathematical model

Abstract: We have developed and validated a new mathematical model to predict successful management of first trimester miscarriage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…10,17,20 This has led to the research for predictors for successful expectant management with lesser complications. [18][19][20][21][22][23] Vaginal bleeding at presentation, maternal age and early gestational age were found positively correlated to successful expectant management. [18][19][20][21] Diagnosis of incomplete miscarriage at primary scan reported higher success rates than those that included only women with missed or anembryonic pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,17,20 This has led to the research for predictors for successful expectant management with lesser complications. [18][19][20][21][22][23] Vaginal bleeding at presentation, maternal age and early gestational age were found positively correlated to successful expectant management. [18][19][20][21] Diagnosis of incomplete miscarriage at primary scan reported higher success rates than those that included only women with missed or anembryonic pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] This has led investigators to study about different selection criteria which could reliably predict the likelihood of a complete spontaneous resolution of pregnancy. [18][19][20][21][22][23] Proper selection of cases for expectant management of early pregnancy miscarriages could result in higher success rate with lesser complications thereby increasing its acceptability. [20][21][22][23] This study was to investigate difference in success rate and complication in expectant management of early pregnancy miscarriages with regard to the type of miscarriage: anembryonic pregnancy, early fetal demise and incomplete miscarriage.…”
Section: Introductionmentioning
confidence: 99%
“…Papaioannou et al [30] reported that first trimester bleeding increased the risk of PTL. Other previous studies [31,32] showed that the possibility of PTL is more in pregnant women with the first trimester bleeding due to many placental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A mathematical model to predict successful expectant management of missed and incomplete miscarriages was validated in a recent prospective study (Casikar et al, 2013). The data were separated into three groups; missed miscarriage, anembryonic sac and incomplete miscarriage, and the authors found that the most independent prognostic variables for their model are the type of miscarriage at primary scan, vaginal bleeding and maternal age.…”
Section: Discussionmentioning
confidence: 99%